Pre-pregnancy body mass index and risk of macrosomia: glycemic status-specific thresholds and subgroup interactions in a prospective cohort - Wu, Yuhang; Xiao, Hanyu; Chen, Lizhang; Qin, Jiabi; Wang, Tingting (Frontiers in Nutrition, 2025)
BackgroundMacrosomia, a critical perinatal complication, is closely linked to maternal obesity and gestational diabetes mellitus (GDM). However, the extent to which GDM status modifies the association between pre-pregnancy body mass index (BMI) and macrosomia, particularly across demographic subgroups, remains poorly understood. This study aimed to quantify glycemic status-specific risk thresholds and explore subgroup interactions in a large prospective cohort.MethodsIn this prospective cohort study, 34,031 women initiating antenatal care before 14 weeks of gestation were enrolled at a tertiary hospital in Central China (2013–2019). Participants were stratified by GDM status and pre-pregnancy BMI categories. Multivariable logistic regression, restricted cubic spline (RCS) models, and interaction analyses evaluated associations between BMI and macrosomia (birth weight ≥ 4,000 g), adjusting for sociodemographic, behavioral, and clinical covariates.ResultsMacrosomia incidence was markedly higher in GDM (6.2%) vs. non-GDM pregnancies (3.6%). Adjusted models revealed a steeper dose–response gradient in GDM: each 1-unit BMI increase conferred 24% higher odds (aOR: 1.24 [95% CI 1.20, 1.28]) in GDM vs. 13% (aOR: 1.13 [1.11, 1.15]) in non-GDM. Obesity amplified risk 6.80-fold (aOR: 6.80 [4.02, 11.51]) in GDM vs. 4.70-fold (aOR: 4.70 [3.12, 7.10]) in non-GDM. RCS models identified nonlinear trajectories in both GDM and non-GDM pregnancies (reference level: 22.94 kg/m2 for GDM and 25.10 kg/m2 for non-GDM). Significant interactions were observed in GDM pregnancies, and the association between pre-pregnancy BMI values and macrosomia was stronger in women < 35 years (aOR: 1.29 vs. ≥35 years, aOR: 1.15), primigravida (aOR: 1.61 vs. multigravida, aOR: 1.18), primiparous (aOR: 1.36 vs. multiparous, aOR: 1.18), and female infants (aOR: 1.29 vs. male, aOR: 1.20). In non-GDM pregnancies, only parity (primiparous, aOR: 1.08 vs. multiparous, aOR: 1.19) and gravidity (primigravida, aOR: 1.05 vs. multigravida, aOR: 1.19) modified the pre-pregnancy BMI-macrosomia relationship.ConclusionGDM status modifies pre-pregnancy BMI-associated macrosomia risks, with distinct thresholds and subgroup vulnerabilities. These findings necessitate glycemic status-specific clinical guidelines and precision interventions targeting high-risk subgroups. Universal preconception weight optimization remains pivotal for non-GDM populations. This study underscores the urgency of integrating metabolic and demographic heterogeneity into perinatal care to mitigate the dual epidemics of overweight/obesity and GDM.